Analysis Of Determinants Of Firm Value In Property And Real Estate Companies Listed On The Bei In 2019-2022 - Sari, Habibah Nurmala; Khaeruni, Ratnawati; Budianto, Erwin (Al-Makki Publisher, 2024)
This study aims to analyze and determine the effect of profitability as measured by return on assets, solvency as measured by debt to equity ratio to company value measured by price book value. This research uses quantitative methods with secondary data sources in the form of the company's annual financial statements. The population of this study is property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. The sampling technique used purposive sampling, and a sample of 37 companies was obtained. The data analysis technique uses multiple linear regression with the SPSS 25 program. The results showed that the return on assets and debt-to-equity ratio had no effect on the value of the company.